Effects of the colour and design of a new pelvic examination chair on comfort during gynaecological examination - C. Stenfelt (Clinical and Experimental Obstetrics & Gynecology, 2020)
Objectives: The main question was whether the colour of a new design of pelvic examination chair could affect how the examination procedure was perceived. A prototype was constructed without vertical leg support and with built-in heating in the upholstery. To improve integrity, the perineum was exposed only during the examination. Main Outcome Measures: The patients were invited to evaluate the two different chair colours used, light blue and off-white, respectively. After vaginal ultrasound, the patients answered an anonymous questionnaire about their experience of the examination and how they perceived the comfort, warmth, integrity and colour of the chair. There were also questions regarding the absence of vertical leg support. Results: The questionnaire evaluation demonstrated the importance of colour since integrity was rated significantly higher in the light-blue chair than in the off-white. Similarly, the blue chair was experienced as significantly more comfortable than the white. Conclusions: The effect of colour was investigated in a new pelvic examination chair without vertical leg support, developed to suit men, women and also non-binary and transgender persons. It was also designed for increased comfort and integrity. The experience of colour had a significant positive (p < 0.001) effect on how the comfort, integrity and the absence of vertical leg support were perceived.